Dampak Transformasi Digital dan Kemajuan Teknologi terhadap Kinerja Organisasi - Raysharie, Puput Iswaudyah; Benius, Benius; Jati, Arya Rozaq Premana; Uke, Rizki Arfandi; Marbun, Ester Talenta Novjalia; Simamora, Novita Sari; Agatha, Ferty; Aurelia, Eghydea Kumala; Aulia, Syifa; Nesya, Olivia Julia; Saputri, Tiara (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
In today's modern business environment, organizations are faced with the challenge of adapting to the times in order to improve their performance. To keep up with the times, organizations need to effectively utilize digital transformation, business strategies, and modern technology. This research aims to investigate the interaction between digital transformation, business strategy, technological advancements, and their impact on organizational/company performance. Literature research method was used with data collected from various journals, including companies that have undergone technological transformation, have business strategies, and utilize technological advancements that impact organizational performance. The research results show that business strategy, digital transformation, and utilization of technological advancements have a positive influence on organizational/company performance.